irpll Jirga: A Mechanism of Dispute Settlement among the Pakhtuns of Peshawar: Irfan Ullah ,Sami ud Din,Sajjad Ali) - jan, abdullah (JPL, 2023)
“Democracy is not alien to the Pukhtuns, as they are carrying on their typical and rudimentary form of government on democratic principles since times immemorial. A unique feature of tribal life is the Jirga system, a council or assembly of elders, which closely resembles the Athenian democracy of the City States of ancient Greece. The Pukhtuns practiced this participatory sort of democracy long before, Lock, Rousseau, and other eminent philosophers expounded their theories about democracy”.